Annual Report 2005-2006 - (:unkn) unknown (Planning Commission, 2014)
The Planning Commission was constituted in March, 1950 by a Resolution of the Government of India, and it works under the overall guidance of the National Development Council. The Planning Commission consults the Central Ministries and the State Governments while formulating Five Year Plans and Annual Plans and also oversees their implemcnation. The Commission also functions as an advisory Planning body at the apex level.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Role; Composition and Functions; Economy and the Plan: An Overview; The Plan; National Knowledge Commission; Environment & Forests Division; Financial Resources Division; Economic Advisory Council to the Prime Minister; Health; Nutrition & Family Welfare Division; Housing and Urban Development Division; Industry'Division (including Coal Unit)